The Differentiation of Human Cytomegalovirus Infected-Monocytes Is Required for Viral Replication - Min, Chan-Ki; Shakya, Akhalesh K.; Lee, Byeong-Jae; Streblow, Daniel N.; Caposio, Patrizia; Yurochko, Andrew D. (Frontiers in Cellular and Infection Microbiology, 2020)
Viral dissemination is a key mechanism responsible for persistence and disease following human cytomegalovirus (HCMV) infection. Monocytes play a pivotal role in viral dissemination to organ tissue during primary infection and following reactivation from latency. For example, during primary infection, infected monocytes migrate into tissues and differentiate into macrophages, which then become a source of viral replication. In addition, because differentiated macrophages can survive for months to years, they provide a potential persistent infection source in various organ systems. We broadly note that there are three phases to infection and differentiation of HCMV-infected monocytes: (1) Virus enters and traffics to the nucleus through a virus receptor ligand engagement event that activates a unique signalsome that initiates the monocyte-to-macrophage differentiation process. (2) Following initial infection, HCMV undergoes a “quiescence-like state” in monocytes lasting for several weeks and promotes monocyte differentiation into macrophages. While, the initial event is triggered by the receptor-ligand engagement, the long-term cellular activation is maintained by chronic viral-mediated signaling events. (3) Once HCMV infected monocytes differentiate into macrophages, the expression of immediate early viral (IE) genes is detectable, followed by viral replication and long term infectious viral particles release. Herein, we review the detailed mechanisms of each phase during infection and differentiation into macrophages and discuss the biological significance of the differentiation of monocytes in the pathogenesis of HCMV.